Reduction of Internet pricing in Malaysia and its relationship to the revolution of digital content - Daud, Mahyuddin (2019)
Internet access has become very extensive in the Southeast Asian region. Thailand and Singapore managed to provide great broadband access and speed, both on wired and mobile connections at low costs. To a greater extent, Internet access has been mooted to form part of the modern living necessity, which qualifies it to be a labelled as human right. Despite the increased Internet penetration in Malaysia, particularly in urban areas, there lies issues over expensive costs of subscription to high-speed broadband services. As consumers have no option but to opt for packages with expensive rate of subscription, there lies a great deal of uncertainty as to whether the Internet is exclusively meant for the elites. If such is the case, one cannot hope that the proposition to transform ‘Internet access’ as human right to be realised in a near future. At the same time, high costs to Internet access may well be translated into impeding growth of digital content as will be seen in this paper. Since this is a work in-progress, some of the popular Internet-pricing models and how adoption of these models may have its relation to the growth of digital content will be analysed. It is hypothesised that when Internet-pricing is reduced, it translates into positive impact to promoting evolution of digital content.